Market Demand and Availability of Chrysanthemum Cut Flowers at the Farmer Level in Tutur Subdistrict - Alfiani, Fina; Soedarto, Teguh; Atasa, Dita; Yektiningsih, Endang (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2025)
Tutur District is the center of chrysanthemum cut flower production in East Java, but there is a discrepancy between the quality of production and market demand. The purpose of this study is to analyze the suitability of the quality of cut chrysanthemum flowers with market desires and determine the price equilibrium point and the number of demand-supply. The method used was quantitative descriptive, with primary data collection through questionnaires and interviews with 56 farmers and 6 chrysanthemum collectors. Data analysis was carried out using gap analysis and market balance analysis through simple linear regression. The results of the study show qualities such as the rate of damage, the rate of bloom and the number of florets still show gaps. The equilibrium point for the price of standard type chrysanthemums is IDR 1,145/stalk with a total of 227,730 stalks, and for the spray type is IDR 1,041/stalk with a total of 441,129 stalks. Farmers tend to sell below the equilibrium price so that there is an excess supply. The quality of chrysanthemums is relatively good but does not fully meet market standards. Policy recommendations include improving farmers' technical skills, providing superior varieties, and timing of harvests to align with peak market demand.